The Romanian Superior Council of Magistracy’s Role in the Protection of The Law Enforcement - Dragoș Călin (Fakultas Hukum Universitas Lampung, 2021)
The Romanian Superior Council of Magistracy (RSCM) has failed to provide stability as an active form of involvement to defend the judicial officers against acts that injures their independenc, impartiality, and professional reputation. The disrespect towards the juidical officers through the media have not motivated the RSM to take any actions. This is not aligned with their responsibility to clarify any miss-leading information. The RSCM has yet to overcome the flawed integrity of the judiciary system.